ANALISIS STATISTIK PERTANDINGAN PADA POSISI BERMAIN CENTER CABOR BOLA BASKET TIM POMNAS JATIM PUTRA - Noval Dailami, Rahmad; Himawan, Agus; Putri Purwoto, Septyaningrum; Yuli Handayani , Heni (Fakultas Ilmu Keolahragaan Unimed, 2024)
The purpose of this research is to find out the results of the statistical analysis of matches in the center playing position for the POMNAS East Java Men's Basketball Team. In this research the author used a quantitative research method using a descriptive type. The population and sample in this study is the center playing position on the men's East Java Pomnas team who played in the